Clearance Systems in the Brain, From Structure to Function - Liu, Jiachen; Guo, Yunzhi; Zhang, Chengyue; Zeng, Yang; Luo, Yongqi; Wang, Gaiqing (Frontiers in Cellular Neuroscience, 2022)
As the most metabolically active organ in the body, there is a recognized need for pathways that remove waste proteins and neurotoxins from the brain. Previous research has indicated potential associations between the clearance system in the brain and the pathological conditions of the central nervous system (CNS), due to its importance, which has attracted considerable attention recently. In the last decade, studies of the clearance system have been restricted to the glymphatic system. However, removal of toxic and catabolic waste by-products cannot be completed independently by the glymphatic system, while no known research or article has focused on a comprehensive overview of the structure and function of the clearance system. This thesis addresses a neglected aspect of linkage between the structural composition and main components as well as the role of neural cells throughout the clearance system, which found evidence that the components of CNS including the glymphatic system and the meningeal lymphatic system interact with a neural cell, such as astrocytes and microglia, to carry out vital clearance functions. As a result of this evidence that can contribute to a better understanding of the clearance system, suggestions were identified for further clinical intervention development of severe conditions caused by the accumulation of metabolic waste products and neurotoxins in the brain, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD).